Overexpression of Pennisetum purpureum CCoAOMT Contributes to Lignin Deposition and Drought Tolerance by Promoting the Accumulation of Flavonoids in Transgenic Tobacco - Song, Jian-Ling; Wang, Ze-Yu; Wang, Yin-Hua; Du, Juan; Wang, Chen-Yu; Zhang, Xiang-Qian; Chen, Shu; Huang, Xiao-Ling; Xie, Xin-Ming; Zhong, Tian-Xiu (Frontiers in Plant Science, 2022)
Elephant grass (Pennisetum purpureum) is a fast-growing and low-nutrient demand plant that is widely used as a forage grass and potential energy crop in tropical and subtropical regions of Asia, Africa, and the USA. Transgenic tobacco with the PpCCoAOMT gene from Pennisetum purpureum produces high lignin content that is associated with drought tolerance in relation to lower accumulation of reactive oxygen species (ROS), along with higher antioxidant enzyme activities and osmotic adjustment. In this study, transgenic tobacco plants revealed no obvious cost to plant growth when expressing the PpCCoAOMT gene. Metabolomic studies demonstrated that tobacco plants tolerant to drought stress accumulated flavonoids under normal and drought conditions, which likely explains the observed tolerance phenotype in wild-type tobacco. Our results suggest that plants overexpressing PpCCoAOMT were better able to cope with water deficit than were wild-type controls; metabolic flux was redirected within primary and specialized metabolism to induce metabolites related to defense to drought stress. These results could help to develop drought-resistant plants for agriculture in the future.